Bimbingan Teknis Pementasan Teater dalam Melestarikan Teater Tradisi Lombok - Sunardy Kasim; Murianto; Syamsurrijal; Abdul Muhid; Diah Supatmiwati (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
The Community Service Activity in the form of Technical Guidance (bimtek) on Traditional Theatre is a collaborative effort between Bumigora University Mataram and Bale Agung Ajar Wali Foundation to support the development and preservation of traditional theatre arts in the region. This activity aims to provide an in-depth understanding of traditional theatre arts and train participants in various aspects of traditional theatre performance, including acting, dance movements and traditional music. In this activity, participants are encouraged to actively participate in presentation sessions, discussions and practical exercises where they can apply the concepts learnt in practical situations. The material presented covered the history, techniques and basic skills of traditional theatre arts, as well as the cultural values contained within them. The results of this activity showed that all participants followed all the materials well and the results of the traditional theatre practice sessions were also very satisfactory. The overall evaluation showed a high level of satisfaction of the participants with the activity as a whole, as well as positive impressions of the quality of the materials and the organization of the event.